'Hyper'-Urbanisation and migration: A security threat. (January 2021) - Awasthi, Soumya
Abstract: Migration is often presented as a threat to national sovereignty and state security. It is time to formulate an alternative discourse - Urbanisation leading to migration (internal) and security threats in the state. 'Hyper-Urbanisation' in the form of 'Smart Cities' which involves rapid infrastructural development, and advanced capital investments occasionally becomes drivers for a threat to security. It is essential to look at the relation between Urbanisation and Migration from a security point of view. Urbanisation often leads to the exclusion of the village communities from the national mainstream development program. The exclusion and politicisation of migrants on the religious and political grounds causes resentment, making them anti-establishment. This paper aims to look at the relationship between urbanisation and internal migration and the challenges of health, education, employment, lack of natural resources and security threat. The paper discusses the two theories of Culture of Poverty theory and Social Disorganization theory and elaborates about the challenges that migrants face in the urban spaces causing denial of integration. Highlights: It is a commentary on the Smart City project of India. Highlights the consequences of Hyper Urbanisation Points out at problems like internal migration, quality of life, security threats The certain recommendation in the context of the Indian case Move from Smart city to Smart Villages